Quality of life of patients living with a stoma and association with the socio-demographic factors - Abdul Wahab, Patimah; Mohamed, Nurhazelin; Ismail, Norsuzana (2022)
Introduction: Stoma formation is a lifesaving surgery to help in the excretion of feces or urine from the body. Previous studies showed that stoma could compromise the patient’s quality of life (QoL), and this issue was associated with their background characteristics. This study aimed to assess QoL and association with the socio-demographic factors among the patients living with a stoma. Methods: A retrospective study was conducted in a teaching hospital in Pahang. Medical records starting from November 2018 until November 2020 were examined, resulting in 48 patients with stoma were selected. Telephone interviews using structured questionnaires were conducted to collect data on socio-demographic and QoL. Quality of Life Questionnaire for a Patient with an Ostomy (QoL-O) was used to measure the QoL of patients living with a stoma. The maximum score was 10, and the minimum score was 0. Result: 24 patients enrolled in this study (response rate = 50%). Their mean age was 56.8 (SD = 18.6) with 70.8% were men (n = 17) and 29.2% were women (n = 7). Almost all were Malay (95.8%) and 79.2% completed secondary school and above. Only 20.8% were employed, and 79.2% were unemployed or retired. About 58.3% had ileostomy, and 41.7% colostomy. The overall mean score of QoL was 7.1 (SD = 1.0). A significant association was only found between QoL and employment status (p = 0.025). Those employed had higher scores on QoL (8.4, IQR 1.0) compared to the retired group (7.1, IQR 1.0) and the unemployed (6.3, IQR 1.0). Conclusion: Most of the patients living with a stoma in this study had a moderate QoL, which was mainly associated with their employment status. Further research with a greater number of patients is needed to determine their QoL as well as to consider other potential factors that may influence their perspectives on QoL.